Quando a caatinga pega fogo: incêndios na vegetação e a política pública de uso do fogo no Ceará de 2002 a 2022 - Matos, Helaine Saraiva (2023)
The state of Ceará, with its 184 municipalities, has forest fires present throughout its fabric, fragmented in space and time, but forming part of a network that contributes to global climate dynamics. This study aimed to understand the use of fire in the state of Ceará from 2002 to 2022, through the concentration of hot spots and the performance of public policy on the use of fire. The methodology used comprised a qualitative approach with bibliographical research, documentary research, data collection in public institutions involved in the theme, production of cartography and semi-structured interviews. With this thesis, we hope to contribute with a geographical look at the theme in Ceará, considering the environmental interface, but also the human one, of the social groups that make use of fire and contribute to the agrarian spatial organization in the Caatinga with its heterogeneities and forms of resistance and resilience. In a more recent perspective, this study also deals with Integrated Fire Management (IFM) as a possible, desirable and necessary alternative in public policy for the Caatinga, which lacks studies and projects for coexistence with fire, especially in the agrarian space.